A meta-heurística de busca dispersa aplicada no planejamento da expansão de sistemas de transmissão - Arcari, Inedio [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work presents a theoretical analysis and computational implementation of a specialized Scatter Search algorithm to solve the static transmission network expansion planning (TNEP) problem of electric power systems. The objective of such planning problems is to determine a set of circuits among the candidates in which not only satisfy the demands but also the minimum investment cost is at hand. This problem is considered as a complex mixed integer nonlinear programming (MINLP) problem that has a lot of local optimum problem. The scatter search is an evolutionary method with the objective of maintaining a set of diverse and high-quality candidate solutions. The proposed scatter search algorithmhas been applied in engineering optimization problems especially in electric power system problems and has presented high quality solutions. The diversity sets ensure to avoid getting trapped in a local optimum. Another important factor is that the proposed methodology reduces the search space and consequently the number of combinations is reduced. In this work, a high quality solution of TNEP is obtained using the greedy constructive heuristic algorithms such as Garver, and Villasana-Garver-Salon that work based on Transport model and DC model respectively. In this work, in order to generate the initial solutions, a controlled disturbance has been added in the costs of the transmission lines in order to obtain diverse and high quality solutions that lead to find the global optimum for some problems even in the initial generation step. Moreover, the proposed scatter search algorithm presents a local improvement phase during the implementation. In order to show the effectiveness of the proposed algorithm, 5 case studies are conducted such as Garver 6-bars and 15 branches , IEEE 24-bars and 41 branches , South Brazilian 46-bars and 79 branches, Colombian 93-bars and 155 branches, and the North-Northeast 87-bars ...

Neste trabalho é realizada uma análise teórica e a implementação computacional de um algoritmo de Busca Dispersa especializado para resolver o problema de planejamento da expansão de sistemas de transmissão (PPEST) de energia elétrica estático. O problema de planejamento consiste em determinar entre um conjunto de circuitos candidatos, aqueles que quando forem incorporados ao sistema apresentarem o menor custo de investimento possível. Este problema é considerado complexo e difícil de ser resolvido por ser um problema não linear inteiro misto, altamente ilhado, envolvendo “explosões” combinatórias. A meta-heurística de busca dispersa é um algoritmo evolutivo que se propõe a combinar soluções de qualidade e de diversidade do espaço de busca. O algoritmo de busca dispersa desenvolvido apresentou-se altamente eficiente para encontrar soluções de ótima qualidade para todos os problemas testados comparados com a literatura consultada, especializada na área. A garantia da diversidade oferecida pelo algoritmo é adicionada intencionalmente como forma de evitar, ou mesmo avançar por ótimos locais. Outro fato importante é que o método opera sobre um conjunto reduzido de soluções do espaço de busca criteriosamente gerado, que faz reduzir significativamente o número de combinações que são realizadas. Rotinas geradas com a utilização de algoritmos heurísticos construtivos gulosos de Garver e Villasana-Garver-Salon para modelos como o de Transportes e o modelo DC no PPEST apresentaram alto desempenho neste trabalho. Uma perturbação controlada nos custos de instalação das linhas de transmissão foi decisiva para que o processo de geração de soluções (factíveis, diversas e/ou com qualidade) fosse altamente eficiente, sendo possível encontrar o ótimo global em alguns problemas ainda nesta etapa de geração de soluções. Mecanismos de melhoramento local aplicados ...
Keywords: Energia elétrica - Distribuição; Algoritmos; Energia eletrica - Transmissão; Electric power distribution